The Online Training on English for Teaching Science for Primary and Secondary School Teachers: Pelatihan Daring Bahasa Inggris untuk Pengajaran Sains bagi Guru SD, SMP, SMA, dan SMK - Lili Indarti; Udin Syaefudin Saud; Tjutju Yuniarsih; Diding Nurdin (Universitas Lancang Kuning, 2023)
Communication is one of the important 21st century skills to teach to the students. The ability of using international laguage supports the global communication. English is the official international language as the media of communication in all important fields. In order to enable good teaching English in science, teachers need to improve their competence. One of the ways is participating in trainings. In current global era, technology facilitates the trainings effectively. The online training of English for Teaching Science held by BBGP Jawa Barat that previously named PPPPTK IPA was attended by primary and secondary school teachers. It provided the positive impacts of improving knowledge and skill of using English especially in listening, speaking, reading, and writing. The average score gain of pretest and posttest is 26.95. The available data is analysed by counting N-Gain to find out the significance of participants’ improvement and training effectivity. The result shows that the normalized value of the online training of English for Teaching Science is 0,598 indicating fair and the percentage 59,76% shows the quite effectiveness of fulfilment. However, there was only 60% of participants met all training sessions. The obstacles faced by participants were technicals and facility availabilities. Keywords: training, online, English, competence, effectiveness